IMPLEMENTATION OF ISLAMIC RELIGIOUS EDUCATION IN BULDING RELIGIOUS VALUES FOR PARTICIPANTS IN SD ISLAM AMANAH UMMAH SURAKARTA - Fandriyanto, F; Khasanah, Uswatun; Fatimah, Meti (Proceeding of International Conference of Islamic Education, 2023)
Religion is a source of religious values and has a very close relationship to enter into one's soul. To form a human beng who is religious and has religious values within him, directed education is needed. An educational institution should introduce and instill monothesm or faith in students as the initial foundation before students get to know many other disciplines. In this way, teachers in general and teachers of Islamic religious education in particular try to create religious culture and increase religious potential, thereby shaping the personality of students to become human bengs who are faithful, pious and have good morals. The questions and objectives in this research are to find out the process of implementing Islamic religious education in balancing religious values in the Islamic SD Amanah Ummah Surakarta school environment and intracurricular learning carried out by guding Islamic religious education in bulding religious values at SD Islam Amanah Ummah Surakarta. This research is a field research using a qualitative descriptive approach. The data source used was selected purposively and snowball sampling. Data collection was carried out using observation, interview and documentation techniques. While data analysis was carried out by descriptive analysis. The results of this research show that: The implementation of Islamic education in balancing religious values in the SD Islam Amanah Ummah Surakarta environment is carried out well and effectively by implementing it in daily activities such as getting used to saying greetings, shaking hands, polite in speaking, polite in behaving, and respect each other both with teachers and fellow friends. Then related to programs in the scholarly curriculum regarding religion, such as holding TPA, then the Dhuha prayer in congregation, the Dhuhur prayer in congregation, then there is talent development such as tahfidz, speeches, cults for men and also lectures or studies, infaq and also memorizing letters -Selected letters in the Qur'an, then exemplary and discipline given by all school members. Intracurricular learning of Islamic religious education in bulding religious values of SD Islam Amanah Ummah Surakarta students is carried out in a systematic way by using the 2013 curriculum and in accordance with the learning elements. And intracurricular learning is also carried out in a student-centered manner and is maximized on aspects of conceptual and illustrative material as well as providing contextual examples. Then for practice it is done by assessing attitudes and controlling the development of attitudes and religious practices.